Quality of Life Following Endoscopic Resection of Skull Base Tumors - Cavel, Oren; Abergel, Avraham; Margalit, Nevo; Fliss, Dan M.; Gil, Ziv (Journal of Neurological Surgery Part B: Skull Base, 2012)
The objective of the study is to evaluate patients' quality of life (QOL) after endoscopic resection of skull base tumors. We estimated the QOL of 41 patients who underwent surgery for removal of skull base tumors via the expanded endonasal approach (EEA). The Anterior Skull Base Surgery Questionnaire (ASBS-Q), a multidimensional, disease-specific instrument containing 36 items was used. The rate of meningitis and cerebrospinal fluid leak was 1.4 and 0%, respectively. There was one case of uniocular visual impairment. The internal consistency of the instrument had a correlation coefficient (α-Cronbach score) of 0.8 to 0.92. Of 41 patients, 30 (75%) reported improvement or no change in overall QOL. Improved scores were reported in the physical function domain and worse scores in the specific symptoms domain. The most significant predictor of poor QOL was female gender, which led to a significant decrease in scores of all domains. Site of surgery, histology, age and comorbidity were not significant predictors of outcome. This paper further validates the use of the ASBS-Q for patients undergoing endoscopic skull base resection. The overall QOL of patients following endoscopic extirpation of skull base tumors is good. Female patients experience a significant decline in QOL compared with males.
Keywords: quality of life; endoscopy; morbidity; skull base; sinuses; craniofacial